2021
DOI: 10.1093/jn/nxab281
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Machine Learning and Statistical Techniques in Development of a Low-Cost Screening Method Featuring the Global Diet Quality Score for Detecting Prediabetes in Rural India

Abstract: Background The prevalence of type 2 diabetes has increased substantially in India over the past 3 decades. Undiagnosed diabetes presents a public health challenge, especially in rural areas, where access to laboratory testing for diagnosis may not be readily available. Objectives The present work explores the use of several machine learning and statistical methods in the development of a predictive tool to screen for prediabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, prediabetes presents overlapping pathophysiology of impaired insulin sensitivity and secretion [25,26]. Although screening tools for prediabetes have been developed [14,[16][17][18][19][20], this is the first study to develop a model to identify the glucose metabolism status of individuals without diabetes. This model encourages individuals to understand their glucose metabolism status and learn how they should change their lifestyle to prevent diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prediabetes presents overlapping pathophysiology of impaired insulin sensitivity and secretion [25,26]. Although screening tools for prediabetes have been developed [14,[16][17][18][19][20], this is the first study to develop a model to identify the glucose metabolism status of individuals without diabetes. This model encourages individuals to understand their glucose metabolism status and learn how they should change their lifestyle to prevent diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of variable selection and machine learning model resulted in high classification accuracy. Birk et al [16] developed a tool for screening individuals with high FPG using global diet quality score (GDQS) and lifestyle questionnaire responses. In this study, RF, generalized linear mixed model (GLMM), least absolute shrinkage and selection operator (LASSO), and elastic net (EN) were used.…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggested that the artificial neural network classifier based on demographic, lifestyle and anthropometric data was an effective predictive model 39 . Birk et al 40 . applied several ML and statistical methods, combined with survey data from the Food Frequency Questionnaire to calculate a global diet quality score, and developed a predictive tool for screening for prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Birk et al . 40 applied several ML and statistical methods, combined with survey data from the Food Frequency Questionnaire to calculate a global diet quality score, and developed a predictive tool for screening for prediabetes. Findings showed that the model had a positive predictive effect.…”
Section: Discussionmentioning
confidence: 99%
“…The use of machine learning seems an excellent option to work with existing, already validated questionnaires and adapt them to different needs and not have an expert involved to design the questionnaires by hand, but rather use expert knowledge to supervise and validate the machine-learning outcomes. However, to the best of our knowledge, machine learning has mainly been used just to estimate nutrient intake or to detect dietary patterns [ 8 , 9 , 10 ]. Dimensionality reduction methods such as Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) have been used in order to detect correlations between different food groups [ 11 ] also involving data gathered from FFQs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%